Preclinical Characterization of Efficacy and Pharmacodynamic Properties of Finotonlimab, a Humanized Anti-PD-1 Monoclonal Antibody - Yunqi Yao; Xiaoning Yang; Jing Li; Erhong Guo; Huiyu Wang; Chunyun Sun; Zhangyong Hong; Xiao Zhang; Jilei Jia; Rui Wang; Juan Ma; Yaqi Dai; et al. (Pharmaceuticals)
Background/Objectives: Finotonlimab (SCTI10A) is a humanized anti-PD-1 antibody tested in Phase III trials for several solid tumor types. Methods: This study characterized the in vitro and in vivo efficacy, Fc-mediated effector function, and non-clinical PK/PD properties of finotonlimab. Results: The results demonstrated that finotonlimab is effective in stimulating human T cell function in vitro and exhibits marked antitumor efficacy in vivo using both PD-1-humanized and PBMC-reconstructed mouse models. Additionally, finotonlimab exhibited minimal impact on the activation of effector cells via Fc receptor-dependent pathways, potentially facilitating PD-1+ T cell killing. In cynomolgus monkeys, finotonlimab exhibited a nonlinear pharmacokinetic (PK) profile in a dose-dependent manner, and a receptor occupancy rate of approximately 90% was observed at 168 h following a single administration of 1 mg/kg. Finotonlimab’s PK profile (especially Cmax) was better than that of marketed antibodies. Following a 13-week successive administration of finotonlimab, a pharmacodynamic analysis revealed that a sustained mean receptor occupancy of PD-1 molecules on circulating T cells remained at or above 93% for up to 8 weeks, even at a dose of 3 mg/kg, and that there were higher antibody accumulations in different dose groups. Conclusions: Taken together, the preclinical findings are promising and provide the groundwork for evaluating the efficacy and pharmacodynamic characteristics of finotonlimab in clinical trials.